Description of Musculoskeletal Disorders and Work Position in Citrus Farmers at Sukoreno Village, Umbulsari District, Jember - Dian Indah Lestari; Retno Purwandari; Alfid Tri Afandi (Journal of Nursing Science Update (JNSU), 2021)
Musculoskeletal disorder has related to ergonomics. Musculoskeletal disorders are caused by the habit of working position of farmers in carrying out their activities such as lifting or carrying heavy loads, doing repetitive movements and habits of wrong positions at work. The study purposed to identify the percentage of musculoskkeletal disorders and work position on citrus farmers in Sukoreno village, Umbulsari district, Jember. This study used a quantitative approach with 116 farmers using simple random sampling method. The questionnaire used in this study was the Nordic body map to determine musculoskeletal disorders and the Upper Extermity Work Demand Scale Revision (UEWD-R) to determine the habits of farmer's work position. The results showed that 60 farmers (51.7%) had high levels of musculoskeletal disorders and work position when harvesting citrus fruits had the highest average of 70.95% with a maximum value of 24. musculoskeletal disorders felt by Citrus farmers were caused by the work done manually with a long duration of time and requires excessive physical ability so that the impact of muscles that contract during work will caused pain in some of limbs.